Outcomes and affecting factors for ICSI and microTESE treatments in nonobstructive azoospermia patients with different etiologies: A retrospective analysis - Gao, Songzhan; Yang, Xianfeng; Xiao, Xiaoshuai; Yin, Shujun; Guan, Yichun; Chen, Jianhuai; Chen, Yun (Frontiers in Endocrinology, 2022)
Introduction: Nonobstructive azoospermia (NOA) is a common and severe form of male infertility. Microdissection testicular sperm extraction (microTESE) combined with intracytoplasmic sperm injection (ICSI) is an optimal treatment for men with NOA. However, the outcomes and affecting factors of ICSI for NOA patients with different etiologies receiving microTESE treatment are still unclear. Methods: A total of 335 NOA patients undergoing microTESE from January 2017 to December 2021 were included in this retrospective analysis. The patients were divided into five groups (idiopathic, Klinefelter syndrome (KS), Y chromosome microdeletions (YCMDs), cryptorchidism and mumps orchitis) according to the etiologies. The clinical characteristics and outcomes of MicroTESE and ICSI were collected and comparisons were performed between clinical characteristics of patients who had successful sperm retrieval (SSR) and sperm retrieval failure (SRF). Results: The overall SSR rate was 40.90%. SSR rate of the idiopathic group (31.22%) was the lowest and was much lower than that of other groups (KS: 48.65%, 28/58; YCMDs: 60.87%; cryptorchidism: 80.95%; mumps orchitis: 75.00%). The overall fertilization rate was 72.26%. No group differences were found among five groups (idiopathic: 73.91%; KS: 71.43%; YCMDs: 64.29%; cryptorchidism: 70.59%; mumps orchitis: 77.78%). The overall clinical pregnancy rate was 66.67%. No group differences were found among five groups (idiopathic: 68.63%; KS: 65.00%; YCMDs: 44.44%; cryptorchidism: 66.67%; mumps orchitis: 85.71%). The overall live birth rate was 66.67%. No group differences were found among five groups (idiopathic: 71.43%; KS: 53.85%; YCMDs: 50.00%; cryptorchidism: 75.00%; mumps orchitis: 66.67%). For SSR patients, the average age was significantly lower in the idiopathic group, while the average testicular volume was significantly greater in the cryptorchidism and mumps orchitis groups. However, no significant differences were found in the level of follicle stimulating hormone (FSH), luteinizing hormone (LH) and testosterone (T) between patients who had SSR and SRF. Conclusion: Patients with idiopathic NOA had lowest SSR. In addition, the age in idiopathic NOA patients was a predictor for SSR while testicular volume in NOA patients with cryptorchidism and mumps orchitis was a predictor for SSR.